Studi Tingkat Motivasi Belajar Siswa Berdasarkan Hubungan Ibu dan Anak Kelas 5 di SD N 02 Dagen - Nur Amalia; Ainnuna Via Argi Putri (Elementary Teacher Education Program, Majalengka University, 2023)
Student learning motivation plays an important role as a driving force in achieving learning goals. In the learning process, it is important to achieve a balance between the level of student learning motivation and the learning objectives. Each student has a different level of motivation to learn, this is influenced by several factors, one of which is family environmental factors. The purpose of this research was to determine the level of student motivation to learn based on the relationship between mothers and children in grade 5 at SDN 02 Dagen. The relationship studied is the close relationship between mother and child. This research uses a mixed method approach which combines elements of qualitative and quantitative methods. The research subjects were students in class 5 at SDN 02 Dagen and had been selected based on the criteria the researchers needed. The results of the research show that there is an influence of the closeness of mother and child on the level of children's learning motivation. Parents and teachers need to pay attention to and increase children's learning motivation at school, and the role of parents at home must also be carried out well